Chemokines and chemokine receptors in Behçet’s disease - Li, Zhan; Cheng, Linlin; Zhan, Haoting; Li, Yongzhe (Frontiers in Immunology, 2023)
Behçet’s disease (BD), a chronic vascular inflammatory disease, is characterized by the symptoms of ocular lesions, recurrent genital and oral ulcers, skin symptoms and arthritis in addition to neurological, intestinal and vascular involvement. The pathogenesis of BD is poorly understood, and there are no effective laboratory markers for the diagnosis of BD. In addition, BD is presently incurable. Chemokines, a family of small secreted chemotactic cytokines, interact with chemokine receptors and mediate the migration, localization and cellular interactions of inflammatory cells. Several studies have suggested that chemokines and their receptors play an important role in the occurrence and development of BD and that these chemokines along with their receptors can be utilized as biomarkers and therapeutic targets. In the present review, chemokines and chemokine receptors involved in BD and their potential application in diagnosis and therapy have been discussed.